Stereotactic Body Radiotherapy versus Low Dose Rate Brachytherapy for Localised Prostate Cancer: a Cost–Utility Analysis. Issue 11 (November 2017) - Helou, J.; Torres, S.; Musunuru, H.B.; Raphael, J.; Cheung, P.; Vesprini, D.; Chung, H.T.; D'Alimonte, L.; Krahn, M.; Morton, G.; Loblaw, A.
Abstract: Aims: To conduct a cost–utility analysis comparing stereotactic body radiotherapy (SBRT) with low dose rate brachytherapy (LDR-BT) for localised prostate cancer (PCa). Materials and methods: A decision-analytic Markov model was developed from the healthcare payer perspective to simulate the history of a 66-year-old man with low-risk PCa. The model followed patients yearly over their remaining lifetimes. Health states included 'recurrence-free', 'biochemical recurrence' (BR), 'metastatic' and 'death'. Transition probabilities were based on a retrospective cohort analysis undertaken at our institution. Utilities were derived from the literature. Costs were assigned in 2015 Canadian dollars () and reflected Ontario's health system and departmental costs. Outcomes included quality-adjusted life years (QALYs), costs and incremental cost-effectiveness ratios. A willingness-to-pay threshold of 50 000/QALY was used. Results: SBRT was the dominant strategy with 0.008LYs and 0.029QALYs gained and a reduction in cost of 2615. Under base case conditions, our results were sensitive to the BR probability associated with both strategies. LDR-BT becomes the preferred strategy if the BR with SBRT is 1.3*[baseline BR_SBRT] or if the BR with LDR-BT is 0.76*[baseline BR_LDR-BT]. When assuming the same BR for both strategies, LDR-BT becomes marginally more effective with 0.009QALYs gained at a cost of 272 848/QALY. Conclusions: SBRT represents an economically attractive radiation strategy. Further research should be carried out to provide longer-term follow-up and high-quality evidence. Highlights: A cost–utility analysis comparing stereotactic body radiotherapy (SBRT) with low dose rate brachytherapy in the treatment of localised prostate cancer was conducted. A decision-analytic Markov model was developed from the Ontario healthcare payer perspective. SBRT is an economically attractive radiation strategy.